Correlation between Edentulism, Nutrition, and Diabetes: A Review - Ajay Singh (Highlights on Medicine and Medical Research Vol. 12, 2021)
With rising of the general global population there also an increase in the number of elderly people which ultimately increase in the edentulism. Moreover, the elderly population is affected by systemic and metabolic diseases, most commonly being Diabetes Mellitus along with nutritional deficiency. Also, nutritional deficiency may develop due to the inability of the elderly population to chew food properly due to loss of teeth following various reasons and leading to complete or partial edentulism. This review is aimed to find a correlation between, edentulism, nutrition, and diabetes and can the treatment of edentulism has an effect on the improvement of nutritional status in diabetic patients.